Analysis of Factors that Influence Low Learning Motivation in Mathematics Learning - Anggi Rismawati; Diandra Yuliana Dewi (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
This study analyzes the factors affecting the low learning motivation of students in mathematics learning at SMA Negeri 5 Magelang using a qualitative descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that effective classroom management, including a well-organized environment, varied teaching methods, and clear rules, can enhance learning motivation. Positive teacher-student interactions, constructive feedback, and emotional support also help boost students' confidence. Active participation in group discussions and collaborative activities further contributes to increased student motivation. In conclusion, effective classroom management and supportive interactions can address the low learning motivation of students in mathematics learning and improve their academic performance.